2021
DOI: 10.1111/srt.13008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the morphometric parameters of pig ear hair follicles

Abstract: Background: Porcine ear skin is used in studies of percutaneous penetration as a substitute for human skin. The objective of the present study was to determine the structure of the hair follicles on the dorsal area of porcine ear skin and make a morphometric comparison with the hair follicles of human skin. Materials and Methods:Sections of frozen biopsies were cut vertically to the skin surface in longitudinal sections using a cryotome and were investigated using microscopy. For each hair follicle, various pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A PP filter with a pore size of 70 m was selected as a model membrane because the diameter of hair follicles at the skin surface of pig ear is reportedly 113±43 μm, similar to that of human skin. 22) In addition, the surface free energy and its dispersion components of PP which affect the wettability or adhesion of a formulation to a skin surface, 23) are similar to that of human and pig skin. 24) The permeation of DiI was used as a tracer of vehicle permeation through PP.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…A PP filter with a pore size of 70 m was selected as a model membrane because the diameter of hair follicles at the skin surface of pig ear is reportedly 113±43 μm, similar to that of human skin. 22) In addition, the surface free energy and its dispersion components of PP which affect the wettability or adhesion of a formulation to a skin surface, 23) are similar to that of human and pig skin. 24) The permeation of DiI was used as a tracer of vehicle permeation through PP.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…Recently, follicular uptake was also shown for lipid-based nanoparticles on the pig ear model. While the pig ear model is suitable to demonstrate HF penetration due to high similarity, it is a tissue that cannot be cultured over a longer time. The lack of cultivability limits the use of biological efficacy and tissue or immune response.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that porcine ear skin is a well suitable skin model for penetration studies [22,23]. This becomes superior when it comes to the investigation of follicular and transfollicular penetration since the skin remains fixed on the cartilage.…”
Section: Introductionmentioning
confidence: 99%